2012
DOI: 10.1111/j.1468-0009.2012.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

What Counts? An Ethnographic Study of Infection Data Reported to a Patient Safety Program

Abstract: Context: Performance measures are increasingly widely used in health care and have an important role in quality. However, field studies of what organizations are doing when they collect and report performance measures are rare. An opportunity for such a study was presented by a patient safety program requiring intensive care units (ICUs) in England to submit monthly data on central venous catheter bloodstream infections (CVC-BSIs). Methods:We conducted an ethnographic study involving ∼855 hours of observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 57 publications
1
112
0
Order By: Relevance
“…In addition, further study of the microprocesses associated with board governance is required. 103 Although qualitative and case study research is beginning to emerge in this area, 59,70 further study of the practices undertaken in the boardroom would provide much-needed insight into exactly how patient safety governance is exercised and experienced. Despite growing pressures for boards to improve and emerging evidence that more effective board oversight is associated with higher quality of care, efforts to create effective governance for quality and patient safety are in its early stages.…”
Section: Methodological and Theoretical Developmentmentioning
confidence: 99%
“…In addition, further study of the microprocesses associated with board governance is required. 103 Although qualitative and case study research is beginning to emerge in this area, 59,70 further study of the practices undertaken in the boardroom would provide much-needed insight into exactly how patient safety governance is exercised and experienced. Despite growing pressures for boards to improve and emerging evidence that more effective board oversight is associated with higher quality of care, efforts to create effective governance for quality and patient safety are in its early stages.…”
Section: Methodological and Theoretical Developmentmentioning
confidence: 99%
“…143 From this perspective, the distortion of indicators occurs not as a deliberate attempt to manipulate the system, but as a result of clinicians attempting to make sense of inherently subjective and messy criteria in the face of uncertainty. 144 Another potential unintended consequence is for clinicians to avoid treating sicker patients to avoid poor publicly reported outcomes. For example, in a news bulletin following the announcement of plans to extend the publication of surgical mortality rates to other specialties, the chairperson of the British Medical Association's Consultants Committee expressed concern that: 145 Some surgeons are deterred from taking on very complex, high-risk procedures because published simplistic league tables count against them.…”
Section: Bevan and Hoodmentioning
confidence: 99%
“…Previous research has demonstrated important differences among hospitals in methods of HAI surveillance and application of definitions. 11,27,28 Implementation of automated surveillance and, hence, consistent identification of high-risk cases may in the future contribute to more standardized HAI surveillance. 8 Extraction from EHRs was possible for nearly all predictors, although some effort had to be made to standardize data prior to model application and care was taken to ensure the comparability of electronic data sources across hospitals.…”
Section: Discussionmentioning
confidence: 99%